Hepatoprotective effect and antioxidant activity of the hydroalcoholic extract of the fruit of two varieties of Opuntia Megacantha “Tuna” - Enciso, Edwin C. (2020)
The present research work was carried out with the aim of determining the hepatoprotective effect and antioxidant activity of the hydroalcoholic extract of the fruit of two varieties of Opuntia megacantha “tuna”, purple and orange. The total phenol content was determined by the Folin-Ciocalteu method and the flavonoids by the aluminum chloride method. Antioxidant activity by the DPPH, ABTS and FRAP methods; and the hepatoprotective effect by means of an in vivo test in 2-month-old albino rats, weighing between 200 ± 20 g, randomly distributed in seven groups of 5 animals each, which received: group I (physiological serum), group II ( CCl4), group III (silymarin), groups IV and V (extract of purple prickly pear at 250 and 500 mg/kg), groups VI and VII, (extract of orange prickly pear at 250 and 500 mg/kg). In blood serum, the activity of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) was determined and the histopathological study of the liver was performed. The purple variety had a higher content of total phenols, flavonoids and antioxidant activity in relation to the orange variety (p<0.05). The activity of AST and ALT at the dose of 250 mg/kg are statistically similar to that of silymarin for extracts of purple and orange prickly pear. In the histopathological study, both varieties showed protection against carbon tetrachloride damage. In conclusion, the hydroalcoholic extract of the purple and orange prickly pear varieties were shown to have a hepatoprotective effect and antioxidant activity.